Ethnic fragmentation, conflict, displaced persons and human trafficking: An empirical analysis - Randall K. Q. Akee; Arnab K. Basu; Nancy H. Chau; Melanie Khamis (Institute for the Study of Labor (IZA), 2010)
Ethnic conflicts and their links to international human trafficking have recently received a surge in international attention. It appears that ethnic conflicts exacerbate the internal displacement of individuals from networks of family and community, and their access to economic and social safety nets. These same individuals are then vulnerable to being trafficked by the hopes of better economic prospects elsewhere. In this paper, we empirically examine this link between ethnic fragmentation, conflicts, internally displaced persons (IDPs), refugees and international trafficking, making use of a novel dataset of international trafficking. We conduct a direct estimation, which highlights the ultimate impact of ethnic fragmentation and conflict on international trafficking through internal and international displacements.
urn:nbn:de:101:1-201010133345
Keywords: R23; D74; O11; Z12; 330; ethnic fragmentation; conflict; displaced persons; human trafficking; Ethnische Beziehungen; Konflikt; Bürgerkrieg; Menschenhandel; Schätzung; Welt